The impact of Nitrogen and Carbon Sources on the Biofilm Formation of Micrococcus luteus - Mahmood, Alan Ahmed; Qader, Mina Kawa; Mahmood, Barzhawand Ahmed; Salih, Lavin Peshraw Hama (Sulaimani Journal for Pure and Applied Sciences, 2021)
This study is conducted to show the influence of different media on the extent and pattern of biofilm formation. Trends of newly emerging pathogens continue steadily. Micrococcus luteus is one of those emerging pathogens. Incidental isolations of this bacteria have been recorded from patients with urinary tract infection and/or immunocompromised conditions. Biofilm formation on the surfaces of wound drainage and urinary catheters has been reported to be the source of recurrence and colonization of the pathogen in those patients. The current study's approach assesses the role of nutrient availability on the patterns of attachment till detachment and dispersion of the biofilms. Different species of bacteria are used to correlate their biofilm formation trend. Micrococcus luteus was chosen in the study due to its emerging pathogenic potential. Validation of biofilm formation is provided by involving Proteus mirabilis; which is an ideal biofilm producer, in parallel with Micrococcus luteus throughout the entire experimental settings. The findings of this study confirm statistically significant differences in biofilm formation patterns when nutritionally different culture media have been utilized to resemble possible environments for the pathogen. Micrococcus luteus has been found to possess the highest potential to produce biofilm in peptone water media where it over paced Proteus mirabilis. Results of the study reveal that both availability and scarcity of carbon and nitrogen sources can influence both positively and negatively on the patterns of biofilm formation by different strains of bacteria and incubation time. Biofilm assessment is an inevitable technique for nosocomial infections due to the complications of antibiotic susceptibility trends that prolong the hospitalization process, which limits treatment capacity.
Keywords: Biofilm; Micrococcus luteus; Proteus mirabilis; Microtiter Plate Assay